Interaction between peripheral blood mononuclear cells and Trypanosoma cruzi-infected adipocytes: implications for treatment failure and induction of immunomodulatory mechanisms in adipose tissue - Moreira, Leyllane Rafael; Silva, Ana Carla; Costa-Oliveira, Cíntia Nascimento da; Silva-Júnior, Claudeir Dias da; Oliveira, Kamila Kássia dos Santos; Torres, Diego José Lira; Barros, Michelle D.; Rabello, Michelle Christiane d. S.; de Lorena, Virginia Maria Barros (Frontiers in Immunology, 2024)
Background/Introduction Adipose tissue (AT) has been highlighted as a promising reservoir of infection for viruses, bacteria and parasites. Among them is Trypanosoma cruzi, which causes Chagas disease. The recommended treatment for the disease in Brazil is Benznidazole (BZ). However, its efficacy may vary according to the stage of the disease, geographical origin, age, immune background of the host and sensitivity of the strains to the drug. In this context, AT may act as an ally for the parasite survival and persistence in the host and a barrier for BZ action. Therefore, we investigated the immunomodulation of T. cruzi-infected human AT in the presence of peripheral blood mononuclear cells (PBMC) where BZ treatment was added. Methods We performed indirect cultivation between T. cruzi-infected adipocytes, PBMC and the addition of BZ. After 72h of treatment, the supernatant was collected for cytokine, chemokine and adipokine assay. Infected adipocytes were removed to quantify T. cruzi DNA, and PBMC were removed for immunophenotyping. Results Our findings showed elevated secretion of interleukin (IL)-6, IL-2 and monocyte chemoattractant protein-1 (MCP-1/CCL2) in the AT+PBMC condition compared to the other controls. In contrast, there was a decrease in tumor necrosis factor (TNF) and IL-8/CXCL-8 in the groups with AT. We also found high adipsin secretion in PBMC+AT+T compared to the treated condition (PBMC+AT+T+BZ). Likewise, the expression of CD80+ and HLA-DR+ in CD14+ cells decreased in the presence of T. cruzi. Discussion Thus, our findings indicate that AT promotes up-regulation of inflammatory products such as IL-6, IL-2, and MCP-1/CCL2. However, adipogenic inducers may have triggered the downregulation of TNF and IL-8/CXCL8 through the peroxisome proliferator agonist gamma (PPAR-g) or receptor expression. On the other hand, the administration of BZ only managed to reduce inflammation in the microenvironment by decreasing adipsin in the infected culture conditions. Therefore, given the findings, we can see that AT is an ally of the parasite in evading the host‘s immune response and the pharmacological action of BZ.